Poskolonialisme: Persepsi Publik Terhadap Indonesian Idol RCTI Oleh Masyarakat Desa Waru Barat Pamekasan - Nur Imamah Imamah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Indonesian Idol is a talent search event that is broadcast live by private national television RCTI which is much loved by the public, especially young people. The purpose of this study was to determine the public's perception of the Indonesian Idol program. This type of research is descriptive qualitative. Data collection techniques with interviews and observations. Data analysis techniques by analyzing data, reducing data, and providing conclusions. The results of the study show that there are 3 things in the public perception, the first is internal perception, namely this event is only for entertainment. The second is external perception, namely there is an element of modern colonialism (postcolonialism). The third is apathy perception, namely the perception that there is no concern for the event.